The gratification paradox: Teacher innovation in urban and rural anti-corruption education - Oktavianus Lintong; Erryl Davy Lumintang; Abdul Haris Kai (Komisi Pemberantasan Korupsi, 2025)
Corruption remains a systemic challenge in Indonesia, yet Anti-Corruption Education (PAK) often fails due to a one-size-fits-all approach. This paper addresses this gap by comparing the implementation of PAK in different urban and regency contexts to inform more effective and contextual strategies. Using an explanatory sequential mixed-methods design, this study surveyed 244 educators in Bitung City and North Bolaang Mongondow Regency. Findings reveal a